Big Data in Digital Markets - Challenges for Competition Policy to Protect Consumer Welfare - Rayhan, Shahi

Network Development of Low-Cost Carriers at German Airports - Joshan, Saeid

Optoelectronic sampling of ultrafast electric transients with single quantum dots - Widhalm, Alex; Krehs, Sebastian; Siebert, Dustin; Sharma, Nand Lal; Langer, Timo; Jonas, Björn; Reuter, Dirk; Thiede, Andreas; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
In our work, we have engineered low capacitance single quantum dot photodiodes as sensor devices for the optoelectronic sampling of ultrafast electric signals. By the Stark effect, a time-dependent electric signal is converted into a time-dependent shift of the transition energy. This shift is measured accurately by resonant ps laser spectroscopy with photocurrent detection. In our experiments, we sample the laser synchronous output pulse of an ultrafast CMOS circuit with high resolution. With our quantum dot sensor device, we were able to sample transients below 20 ps with a voltage resolution in the mV-range.
Keywords: tet_topic_qd

Constitutive modeling of viscoplasticity including phase transformations for graded thermo‐mechanical processing - Westermann, Hendrik; Reitz, Alexander; Mahnken, Rolf; Grydin, Olexandr; Schaper, Mirko (PAMM)

Damage simulation of thermo‐chemo‐elasto‐plastic fibre reinforced composites using mean‐field homogenization methods - Lenz, Peter; Mahnken, Rolf (PAMM)

An uncertainty model for the curing process of transversely fiber reinforced plastics - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (PAMM)

Constitutive modeling of dynamic recrystallization coupled to viscoplasticity - Westermann, Hendrik; Mahnken, Rolf (PAMM)

A deep learning driven uncertain full‐field homogenization method - Henkes, Alexander; Caylak, Ismail; Mahnken, Rolf (PAMM)

A non-equilibrium thermodynamic framework for viscoplasticity incorporating dynamic recrystallization at large strains - Mahnken, Rolf; Westermann, Hendrik (International Journal of Plasticity)

Fuzzy and stochastic approach applied to rubber like materials - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf; Dridger, Alex (Safety and Reliability)

On the Thermodynamics of Dynamic Recrystallization for Viscoplasticity at Large Strains - Westermann, Hendrik; Mahnken, Rolf (14th WCCM-ECCOMAS Congress)

Vom rollfähigen zum programmierbaren Fahrzeug. - Scheibe, Volker; Stein, Gerd; Tenberge, Claudia; Bohrmann, Mareike (Die technische Perspektive konkret. Begleitband 5 zum Perspektivrahmen Sachunterricht.)

Anregungen für die Unterrichtspraxis - empfehlenswerte Literatur. - Tenberge, Claudia (Die technische Perspektive konkret. Begleitband 5 zum Perspektivrahmen Sachunterricht.)

"Wie lang ist der Dinosaurier?" Entwicklung eines Messrads zum Messen gekrümmter Linien. - Austermann, Ulrike; Gais, Berenike; Tenberge, Claudia (Die technische Perspektive konkret. Begleitband 5 zum Perspektivrahmen Sachunterricht.)

Plattformgestaltungen auf digitalen Märkten - eine Analyse der Wohlfahrtseffekte - Ajredini, Zurkani

320 GHz Analog-to-Digital Converter Exploiting Kerr Soliton Combs and Photonic-Electronic Spectral Stitching - Fang, Dengyang; Drayß, Daniel; Lihachev, Grigory; Marin-Palomo, Pablo; Peng, Hui; Füllner, Christoph; Kuzmin, A; Liu, J; Wang, Ruoyu; Snigirev, Viacheslav; Lukashchuk, Anton; Zang, M; et al. (2021 European Conference on Optical Communication (ECOC))
We demonstrate a photonic-electronic analog-to-digital converter (ADC) offering a record-high acquisition bandwidth of 320 GHz. The system combines a high-speed electro-optic modulator with a Kerr comb for spectrally sliced coherent detection and is used for digitizing ultra-broadband data signals.

Inklusionskompetenz von Lehramtsstudierenden im Vergleich dreier europäischer Bildungssysteme – Ergebnisse aus dem Forschungsprojekt. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank

Inklusionskompetenz von Lehramtsstudierenden im Vergleich dreier europäischer Bildungssysteme –Schlussfolgerungen und Implikationen. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank

Determinants for teachers’ intentions to manage heterogeneity in (non-)inclusive primary education. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

Primary school students’ contact experiences and their attitudes towards peers with disabilities. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Löper, Marwin Felix; Schwab, Susanne; Hellmich, Frank